Image-guided biopsy in women with breast cancer presenting with peritoneal carcinomatosis. (1st January 2006) - Hewitt, M. J.; Hall, G. D.; Wilkinson, N.; Perren, T. J.; Lane, G.; Spencer, J. A.
Abstract : When women with a history of breast cancer present with peritoneal carcinomatosis, the differential diagnosis lies between recurrent breast cancer or a new primary tumor. This scenario is of particular relevance to women with a BRCA gene mutation, who have a genetic predisposition to develop second primary tumors of the ovary, fallopian tube, and peritoneum. We describe the use of image-guided core biopsy as an alternative to laparoscopy or exploratory laparotomy in providing minimally invasive diagnosis in this increasingly common clinical dilemma.